The Training of University Teacher Trainee under the Objectives of University Project - Zedam, Amar; Rezig, Manal; Koussa, Lamia (Journal of Human Sciences, 2022)
This study investigated the training of university trainee and its relationship with the quality standards of the university curriculum and program via the analysis of semi-directive interviews to a randomly selected number of teachers at the institute of physical and sports activities as a tool of research to be analyzed.  The results show that the university teacher trainee rely on the academic and  professional training, the availability of scientific and objective training, the development and the improvement of science, the encouragement of pedagogical creativity. The awareness of quality standards among teachers allows the university trainee teacher to renew his lessons to meet the students’ needs through the use of the internet technologies.